Familial Aggregation of Cranial Tremor in Familial Essential Tremor - Louis, Elan D. (2013)
BACKGROUND: Essential tremor (ET) is often familial and phenotypic features may be shared within families. Cranial (neck, voice, jaw) tremor is an important feature of ET. We examined whether cranial tremor aggregates in ET families, after controlling for other factors (age, tremor severity and duration). METHODS: Among ET probands and relatives enrolled in a genetic study at Columbia University (95 subjects in 28 families), we assessed the degree to which occurrence of cranial tremor in the proband predicted occurrence of cranial tremor in affected relatives. RESULTS: Forty-five (47.4%) subjects had cranial tremor on neurological examination (probands 66.7%, relatives 39.7%). Among 28 families, 23 (82.1%) contained individuals with and individuals without cranial tremor, indicating a high degree of within-family heterogeneity. In comparison to subjects without cranial tremor, those with cranial tremor had higher total tremor scores (p<0.001), were older (p=0.003), and had tremor of longer duration (p=0.01). In logistic regression models, the odds of cranial tremor in a relative was not related to occurrence of cranial tremor in the proband (p>0.24). CONCLUSIONS: Cranial tremor did not aggregate in families with ET; the major predictor of this disease feature was tremor severity rather than presence of cranial tremor in another family member.